Which factors determine the long‐term effect of poor early‐life nutrition? A meta‐analytic review. Issue 8 (5th August 2021) - Almeida, L. Zoe; Hovick, Stephen M.; Ludsin, Stuart A.; Marschall, Elizabeth A.
Abstract: Early‐life conditions can have long‐lasting effects (experiential legacies) on an individual's performance. Experiential legacies are an important source of variation among mature individuals because responses to early‐life environments vary widely. Yet, the factors influencing the magnitudes and directions of phenotypic responses to experiential legacies are poorly understood, hindering our ability to predict adult phenotypes and population‐level consequences of environmental stressors. To better understand these issues, we examined how experiential legacies varied with the type of phenotypic response (e.g., reproduction, longevity), characteristics of the individual, and characteristics of the stressful conditions imposed. We conducted a meta‐analytic review ( n species  = 65, n studies  = 81), examining experiential legacies of early‐life nutritional restriction. We found generally consistent negative or neutral impacts of early nutritional stress on later‐life phenotypes, indicating that positive responses to early nutritional restriction may be rare among organisms. Our results also demonstrated differences in how experiential legacies were expressed in specific dimensions of an individual's phenotype; for example, magnitude and direction differed among responses in development rate (weak negative response), offspring quality and quantity (strong negative), and longevity (neutral response). We also found that the harsher the early‐life nutritional stress, the stronger the negative nutritional legacy. Our results emphasize the complicated interactions among a suite of phenotypic responses in determining individual performance. Given the potential for individual performance to inform the demography and dynamics of populations, we offer avenues for future research that can improve our understanding of how experiential legacies of nutrition or other early‐life conditions affect populations.